THE IMPACT OF ROAD TRAFFIC ON THE AIR QUALITY IN CLUJ-NAPOCA: CASE STUDY- NORTH RING ROAD FLOREŞTI – CLUJ-NAPOCA - NISTOR, Elena Larisa; BODOR, Anamaria; OPREA, Marius George; ȘTEFĂNIE, Horațiu (Studia Universitatis Babeș-Bolyai Ambientum, 2019)
In this research, we analysed the impact of road traffic on air quality at the Cluj-Napoca border. For this purpose, the road traffic on the North ring road was monitored: Floreşti (Pădurii Street) - Cluj-Napoca (Donath Street) at the same time with the measurement of the particulate matter PM10. The daily average road traffic was determined according to 'AND 584-2002 normative: "Normative for the calculation of the traffic for the design of the roads from the point of view of the carrying capacity and traffic capacity". For the measurement of particulate matter concentrations PM10, two Dusttrak DRX Aerosol Monitor Model 8533 instruments were used, capable of simultaneously providing mass concentration data for all particle size fractions over a wide range of concentrations (0.001-150 mg/m3) in real time. These were located in two different areas of the ring road: the first instrument was about 20 m from the road on Donath Street in Cluj-Napoca, and the second at a distance of about 80 meters from the road, outside the city.